Negotiating Sharia, Customary Law, and Gender: Feminist Legal Pluralism in the Learo Tradition of Marriage in the Bintauna Community, Indonesia - Rizal Darwis; Nurul Mahmudah; Ahmad Faisal; Muhammad Syakir Al Kautsar; Ahmad Fathan Aniq (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
The learo tradition in marriage among the Bintauna community of Indonesia reflects the tension between Islamic law, customary law and gender equality. While this practice symbolically honours women, it simultaneously enforces a discriminatory public virginity test, causing psychological distress and gender inequality. This study aims to analyse the learo tradition as a space for negotiation between Sharia law and customary law, to uncover power relations and the politics of women’s bodies, and to propose a framework of feminist legal pluralism centred on women’s voices. This qualitative research was conducted in Bintauna Sub-district (May–July 2023) using semi-structured interviews with 18 respondents (religious leaders, customary leaders, ritual leader (inang), academics, and women practising the tradition) and non-participant observation at five learo ceremonies. Thematic analysis was conducted using a feminist legal pluralism framework. The findings indicate: (1) the function of virginity testing within the learo tradition exceeds the bounds of valid customary (‘urf shahih) as it contradicts cover up a fault (saturul ‘aib) and the objectives of Islamic (law maqashid of sharia); (2) this practice reinforces patriarchy by imposing purity tests solely on women, causing trauma and stigma; (3) women (the ritual leader and the bride) have limited but strategic agency in quietly negotiating the rituals. The contribution of this research is to provide an operational framework for feminist legal pluralism based on three pillars: living customary normativity, locally reinterpreted Islamic legitimacy, and dialectical power relations. This framework offers adaptive transformation without erasing tradition, by recommending the abolition of virginity tests, the privatization of rituals, and full inclusivity for all prospective brides and grooms